Population ageing research from a geographical perspective - methodological approach. - Ładysz, Jerzy; Gladkey, Alexander V. (Bulletin of Geography. Socio-economic Series, 2007)
The substance and theoretical fundamentals of development of economic agglomerations are considered. The general laws, principles and methodology of sustainable development of economic agglomerations in a transition economy are investigated. The territorial structure of the Kiev economic agglomeration and the ways to provide its sustainable development are analyzed.